Venom proteome of Malaysian Bungarus candidus and Bungarus fasciatus - Othman, Iekhsan; Ahmad Rusmili, Muhamad Rusdi; Ting, Tee Yee; Hodgson, Wayne C. (2014)
Novel Aspect A first report of natriuretic peptide in Bungarus venom exhibiting hyponatremic effects together with serine protease and different neurotoxins compositions. Introduction Snake envenoming is now considered to be a neglected tropical disease by the World Health Organisation. Mortality and morbidity from snakebite is particularly prevalent in under developed and developing countries. Bungarus candidus and B. fasciatus are two medically important venomous snakes in Malaysia. Even though krait bite is relatively rare in Malaysia, the emergence of newly observed symptoms such as hyponatremia, myotoxicity and cardiovascular effects warrant closer examination of the composition of their venoms. In addition, it has been suggested that monovalent Bungarus fasciatus antivenom is not a suitable treatment of Bungarus candidus envenoming. In this study, we would like to describe proteome and compare composition of Malaysian B. candidus and B. fasciatus venoms by using a "bottom-up" proteomics approach.